Shared Vision: Providing Education as a Preparation for Becoming Leaders in Organizations to Ma'arif High School Students - Febriyanti, Amanda Lintang; Yulyantika, Nadya Rindy; Pramitha, Hening; Sawitri, Nabila Dwi; Romadlona, Nohan Arum; Ardiyani, Novita Rama; Febiana, Viona Riska; Pasambe, Yudea; Sheikh Abdullah, Siti Rozaimah (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2024)
Shared vision is a concept of leadership in which a leader strives to build and share a clear vision with a team member or organization. This activity is carried out at Ma’arif Batu High School with the aim of raising the knowledge of students about shared vision, which can lead them to follow an organization or become its leader. The method used in this examination is the lecture method, which involves conducting a pre- and post-test session to measure the level of knowledge of the participants. The sampling of this dedication uses random sampling techniques in which student and student populations are taken randomly. The data analysis is carried out in the form of a frequency distribution table based on the characteristics of Ma’arif students as respondents and the results of the pre-test as well as the post-test. The success of this dedication can be seen from the increased values of the post-test, where the results are higher than pre-tests. With such results, it can be concluded that the educational activities on Shared Vision are successful. It is hoped that after implementing these educational activities, Ma’arif’s high school students will be able to implement a shared vision in their present and future organizations in order to have a successful and structured organization.